Os estudos sociais da alimentação: cultura, gosto e consumo - Boragnio, Aldana (Universidad Nacional del Litoral, 2021)
Feeding is a behaviour aimed at obtaining the energy to carry out the functions that maintain the organism running as well as the development of its physical-cognitive abilities. However, eating is constituted as a complex system of sociocultural relationships, cohesion and conflict. Therefore, to understand why you eat what you eat we must place this food act within a context, a society, a specific time and space. In cities, the access depends on the market and on the State which is the responsible for the food production, availability, circulation and consumption. This article seeks to propose a theoretical journey from authors that allow us to focus on the intersections and frameworks that emerge from the relationship between food as a cultural fact, taste as a culturally organized and shaped sense, and food consumption in the creation of the current guest as a research object from social studies.